A Rancangbangun Mesin Polisher Beras Skala Laboratorium - Winarto Winarto (Jurnal Ilmiah Teknik Pertanian - TekTan, 2021)
Rice is a plant that is rich in benefits, almost all parts of the rice plant can be used for human and animal needs, this is because in rice plants there are good carbohydrates, energy, nutrition, sugar, food fiber, fat, protein. For humans and animals, of course, it requires several previous processes so that they can be processed into various products. It takes a machine that can polish or whiten the broken rice husks between the rice bran and the bran separately so that it can be processed into the next process. The objectives of this research are to design the polisher engine build, and to test the polisher engine performance. Literature study, machine design, selection of materials and tools to be used, machine manufacturing and assembly, and machine testing are a series of processes for making this machine. The process of polishing cracked rice with a weight of 2.5 kilograms with an average operating speed of 0.1165 hours, an average of 1.23 kg (49%) of cracked rice polishing, an average weight of 0.59 kg of manure and an average yield of 54% average.